Туризм як система - Височан, О. С. (Видавництво Львівської політехніки, 2014)
Досліджено найвідоміші в світовій практиці моделі системи туризму. Розроблено власну модель економічної інформаційної системи туризму (ЕІСТ) та охарактеризовано її елементи і взаємозв’язки між ними. Understanding tourism as a systemic phenomenon is connected with the necessity of structuring the totality of its economic elements and relationships among them to solve basic problems that exist in the tourism sector today. A systematic approach is key to the effective management of tourism at all levels. In the work highlighted two main objectives: to explore the most famous in the world practice of economic system model of tourism; to develop its own model of economic information systems tourism (EIST) and describe its elements and the relationships between them. To do this, the article outlines the basic system model of tourism, which will provide a scientific basis for further research in the field of modeling of tourism as a global socio-cultural phenomenon and tourism from an economic point of view. In particular, models of tourism system such authors: C.A. Gunn, N. Leiper, M.J. Lamont, T. Tkachenko, R. Prosser, R.C. Mill&A.M. Morrison, A. Holden, C. Kaspar, A. Alexandrova, M.L. Miller&J. Auyong, J. Wall&E. Mathieson, V. Gerasymenko. In the author’s model of the tourism system used cybernetic approach to management with allocation of direct and inverse relations of subject and object management, as well as studying the effects of individual elements on the functioning of the system as a whole. The basis of the presented model are three elements: – the tourism industry as a set of production and non-production enterprises and organizations that provide comprehensive travel demand: accommodation, catering, transport companies, tour operators and agents, tourist information and tourdesk, associations, etc.; – market tourism products (services) as a “playground” for the implementation of the product that produces the tourism industry; – the tourist as the end user of the product and the source of demand in the market of tourist services. The relationship of the economic system of tourism with the environment is achieved by the presence of direct impact of environmental, political, social, cultural, technological factors on tourism) and indirect (changes in the environment caused by tourism development) information links. In the future, we have the task to investigate in detail the relationship of the individual elements of the system of tourism, especially with regard to functional subsystems of the tourism industry. Key words: tourism, system, tourist, tourism industry.
Tourism as a system
Keywords: туризм; система; турист; туристична індустрія; tourism; system; tourist; tourism industry